BTN2A2 protein negatively regulates T cells to ameliorate collagen-induced arthritis in mice - Xueping He (Nature Portfolio, 2021)
Abstract Rheumatoid arthritis (RA) is an autoimmune disorder characterized by persistent inflammatory responses in target tissues and organs, resulting in the destruction of joints. Collagen type II (CII)-induced arthritis (CIA) is the most used animal model for human RA. Although BTN2A2 protein has been previously shown to inhibit T cell functions in vitro, its effect on autoimmune arthritis has not been reported. In this study, we investigate the ability of a recombinant BTN2A2-IgG2a Fc (BTN2A2-Ig) fusion protein to treat CIA. We show here that administration of BTN2A2-Ig attenuates established CIA, as compared with control Ig protein treatment. This is associated with reduced activation, proliferation and Th1/Th17 cytokine production of T cells in BTN2A2-Ig-treated CIA mice. BTN2A2-Ig also inhibits CII-specific T cell proliferation and Th1/Th17 cytokine production. Although the percentage of effector T cells is decreased in BTN2A2-Ig-treated CIA mice, the proportions of naive T cells and regulatory T cells is increased. Furthermore, BTN2A2-Ig reduces the percentage of proinflammatory M1 macrophages but increases the percentage of anti-inflammatory M2 macrophages in the CIA mice. Our results suggest that BTN2A2-Ig protein has the potential to be used in the treatment of collagen-induced arthritis models.